2000
DOI: 10.2500/105065800779954338
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sinus Surgery in Patients with Cystic Fibrosis: An Analysis of Complications

Abstract: The application of endoscopic sinus surgery (ESS) for the management of paranasal sinus disease in patients with cystic fibrosis (CF) has been well described. Due to underlying medical issues such as acquired coagulopathies and advanced pulmonary disease, perioperative morbidity is assumed to be higher in this group. The incidence and type of complications associated with CF patients undergoing ESS has not been previously described. We reviewed 52 consecutive endoscopic procedures in 41 patients with CF perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 19 publications
1
23
0
3
Order By: Relevance
“…However, a previous study by Albritton and Kingdom demonstrated a low complication rate for ESS in this patient group, compared to non-CF ESS complication rates reported in the literature [38]. Another previous study did not show association of ESS or open sinus surgery with increased rates of pulmonary complications or postoperative bleeding in CF patients [39].…”
Section: Managementmentioning
confidence: 62%
See 1 more Smart Citation
“…However, a previous study by Albritton and Kingdom demonstrated a low complication rate for ESS in this patient group, compared to non-CF ESS complication rates reported in the literature [38]. Another previous study did not show association of ESS or open sinus surgery with increased rates of pulmonary complications or postoperative bleeding in CF patients [39].…”
Section: Managementmentioning
confidence: 62%
“…Studies on the effect of sinus surgery on pulmonary function have shown improvement of pulmonary symptoms and a reduced need for hositalization, but no differences in pulmonary function test outcomes (grade C evidence) [5558]. No association has been found between sinus surgery and increased rates of postoperative complications, including hemorrhage (grade C evidence) [38, 39]. Surgical revision rates in patients with nasal polyps are much higher than in patients without polyps (grade C evidence) [53].…”
Section: Discussionmentioning
confidence: 99%
“…In CF improvement after FESS is less good than in non-CF children, but still significant with 50% after 2 years [1]. FESS is associated with a lower incidence of tracheobronchitis and pneumonia in CF-patients with a transplanted lung [22].…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have been conducted to report on the safety and effectiveness of FESS in CF patients. 9,[119][120][121][122][123] Complication rate after FESS in CF patients (11.5%) was found to be similar to the rate of non-CF FESS complications (0-17%). 121 Khalid et al reported on the outcomes of sinus surgery in adult patients both with and without CF.…”
Section: Novel Therapeutics: Targeting the Basic Defectmentioning
confidence: 99%
“…9,[119][120][121][122][123] Complication rate after FESS in CF patients (11.5%) was found to be similar to the rate of non-CF FESS complications (0-17%). 121 Khalid et al reported on the outcomes of sinus surgery in adult patients both with and without CF. 114 Although baseline CT and endoscopy scores were significantly worse in CF patients, the overall quality of life improvements as well as the degree of endoscopic improvement was similar between the two groups.…”
Section: Novel Therapeutics: Targeting the Basic Defectmentioning
confidence: 99%